Bridge Structure Study on the Dome of the Boarding School’s Mosque at Pringsewu District in Bandar Lampung - Wijaya, Angga; Kurniawan, Panji; Nafrizal; Risano, A Yudi Eka (INSTEP Network, 2022)
Islamic architecture as a foundation in building Muslim worship facilities in the form of mosques has developed its meaning along with advances in science and technology. One of the concepts in designing a mosque is to ensure that the congregation can close the rows of rows. Based on the verses of the Qur'an regarding the priority of rows in congregational prayers, effort (rashshus shufūf) in congregational prayers is something that is ordered in the Qur'an and hadith.It thenmanifested in the Islamic architectural design of the Klangenan Insan Mulia Boarding School Mosque in the form of providing a center column so that the prayer halls are not interrupted due to the presence of middle columns. As a consequence of the design, the structure of the mosque required several adjustments which were well planned and efficient. This research was conducted using a qualitative method with descriptive analysis supported by modeling simulation and load strength analysis using ETAB V. 16 software, so that the results obtained in the form of structural calculations for steel rafter roof construction using the bridge structure model. The steel rafter roof construction with the bridge structure model was chosen due to several factors including: strength, practicality, and design flexibility.